SOCIOECONOMIC DETERMINANTS OF MATERNAL ANEMIA: A DISAGGREGATED LEVEL ANALYSIS FROM ASSAM, INDIA (Proceedings of the International Conference on Public Health, 2017)
This study examines socio-economic determinants associated with maternal mortality at disaggregated level in Assam, the state with highest maternal mortality ratio in India. An extensive door-to-door household survey was carried out during 2014-15 using multistage sampling to select villages in districts with high number of reported maternal deaths. The samples consist of currently pregnant women, mother with children 0-24 months and members of families who have experienced of maternal death. The study reveals that prevailing incidences of maternal mortality and maternal complications are the result of maternal anemia. Maternal complications are more likely to be associated with lower concentration of hemoglobin level, which is a proxy for maternal anemia. In addition, concentration of hemoglobin level is positively related to socioeconomic factors-literacy, land ownershipand habitat/occupation of the sample population. As a policy prescription, such findings should encourage the policymakers to identify context specific determinants of maternal anemia for appropriate interventions, instead of ‘one-size-fits-all’ type of approach
Keywords: Maternal Anemia, Social Context,Dietary Supplementary, Iron Bioavailability.